Cassava in Asia: Designing crop research for competitive markets - Hershey, Clair H.; Howeler, Reinhardt H. (International Center for Tropical Agriculture, 2001)
This paper reviews cassava in Asia from a broad perspective, culminating in a definition of the research areas that will contribute effectively to development goals in the region. The first section outlines regional trends in production, trade and utilization, drawing comparisons to global trends. A basic tenet of the paper is that the competitive marketplace – at local, regional and international levels – is rapidly changing cassava’s roles in development. Hence, in the second section the discussion is placed in the context of the external social, economic and political environments that impact the cassava sector. The third section then indicates specific constraints and opportunities in the cassava system. Finally, we outline the role of key research areas for the cassava systems of Asia.